2000
DOI: 10.1007/s11908-000-0066-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antimicrobial resistance on the treatment of invasive pneumococcal infections

Abstract: Infectious diseases, such as pneumococcal pneumonia, which were almost invariably lethal in the pre-antibiotic era, caused radically less mortality with the advent of antimicrobial chemotherapy. However, the use, misuse, and abuse of these agents have led to the emergence of antimicrobial resistance. In the past, pneumococci were all exquisitely sensitive to penicillin G. By the late 1960s, penicillin-nonsusceptible Streptococcus pneumoniae (PNSP) was being described. Since then, this problem has achieved epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This pathogen causes significant morbidity and mortality worldwide in both children and adults (12,21,35). Management of pneumococcal disease is also complicated by the increasing rate at which this organism is developing resistance to multiple classes of antimicrobial agents on a global scale (3,25).…”
mentioning
confidence: 99%
“…This pathogen causes significant morbidity and mortality worldwide in both children and adults (12,21,35). Management of pneumococcal disease is also complicated by the increasing rate at which this organism is developing resistance to multiple classes of antimicrobial agents on a global scale (3,25).…”
mentioning
confidence: 99%
“…Current increasing usage of the clinical antibacterial drugs forces antibiotic resistance to occur in both pathogenic and zoonotic bacteria in animals [19]. Previous research showed that the appearance of antibiotics resistant strains can make treatment of bacterial infections more di cult, which may lead to an overall increase in transmission, morbidity and mortality [20,21]. These results suggest that effective treatment should be based on the results of antimicrobial susceptibility tests and clinical e cacy in the control of bacterial infections in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing usage of the clinical antibacterial drug forces the resistance to occur in both pathogenic and zoonotic bacteria in animals [19]. Previous research showed that the appearance of drug resistant strains can make treatment of bacterial infections more difficult, which may lead to an overall increase in transmission, morbidity and mortality [20,21]. These results suggest that effective treatment should be based on the results of antimicrobial susceptibility tests and clinical efficacy in the control of bacteriosis in clinical practice.…”
Section: Discussionmentioning
confidence: 99%